Phytofabricated gold nanoparticles as modulators of salt stress responses in spinach: implications for redox homeostasis, biochemical and physiological adaptation - Amir, Mohammad; Raheem, Abdul; Yadav, Pushpanjali; Kumar, Vijay; Tewari, Rajesh Kumar; Jalil, Syed Uzma; Danish, Mohammad; Ansari, Mohammad Israil (Frontiers in Plant Science, 2024)
The utilization of plant material for synthesizing nanoparticles effectively triggers physiological and biochemical responses in plants to combat abiotic stresses. Salt stress, notably caused by NaCl, significantly affects plant morphology and physiology; leading to reduced crop yields.Understanding the mechanisms of salt tolerance is crucial for maintaining crop productivity. In this study, we examined the effects of 150 μM spinach-assisted gold nanoparticles (S-AuNPs) on various parameters related to seed germination, growth attributes, photosynthetic pigments, stomatal traits, ion concentrations, stress markers, antioxidants, metabolites, and nutritional contents of spinach plants irrigated with 50 mM NaCl. Results showed that S-AuNPs enhanced chlorophyll levels, leading to improved light absorption, increased photosynthates production, higher sugar content, and stimulated plant growth under NaCl stress. Stomatal traits were improved and partially closed stomata were reopened with S-AuNPs treatment, possibly due to K + /Na + modulation, resulting in enhanced relative water content and stomatal conductance. ABA content decreased under S-AuNPs application, possibly due to K + ion accumulation. S-AuNPs supplementation increased proline and flavonoid contents, while reducing ROS accumulation and lipid peroxidation via activation of both non-enzymatic and enzymatic antioxidants. S-AuNPs also regulated the ionic ratio of K + /Na + , leading to decreased Na + accumulation and increased levels of essential ions in spinach plants under NaCl irrigation. Overall, these findings suggest that S-AuNPs significantly contribute to salt stress endurance in spinach plants by modulating various physiological attributes.